Identification and antibiogram study of bacterial species isolated from milk samples of different locations in Bangladesh (Asian Journal of Medical and Biological Research, 2016)
Cows milk containing pathogenic bacteria is an important threat to the consumers. The objectives of the present study were to identify the bacterial agents of public health importance in milk samples (n=35) of different locations and to determine their sensitivity to different antibiotics. The milk samples were collected and transported aseptically and subsequently allowed for culture in bacteriological media, Grams staining and biochemical tests for the identification of bacterial species. The bacteria identified were Staphylococcus aureus, Escherichia coli and Salmonella typhi, and their prevalence, in case of vendor milk specimens (n=28), were 96.43%, 53.57% and 35.71% respectively, and of brand milk specimens (n=7), were 42.86 %, 28.57% and 0%, respectively. This suggests that cautionary measures should be taken for quality milk production and consumption. The antibiotic sensitivity test was done by disc diffusion method and the average inhibition zones, in case of Staphylococcus aureus, were 32 mm for oxytetracycline, 26 mm for amoxicillin, 35 mm for ciprofloxacin, 27 mm for cefotaxime, 30 mm for ceftriaxone, 30 mm for azithromycin, and 26 mm for erythromycin; in case of Escherichia coli, were 5 mm for oxytetracycline, 9 mm for amoxicillin, 22 mm for ciprofloxacin, 30 mm for cefotaxime, 31 mm for ceftriaxone, 15 mm for azithromycin, and 0 mm for erythromycin; in case of Salmonella typhi., were 25 mm for oxytetracycline, 24 mm for amoxicillin, 38 mm for ciprofloxacin, 31 mm for cefotaxime, 34 mm for ceftriaxone, 24 mm for azithromycin, and 0 mm for erythromycin. Therefore, ciprofloxacin and ceftriaxone may be the antibiotics of first choice, and cefotaxime and azithromycin may be the second choice among the test antibiotics for the treatment of illness caused by these bacteria.Asian J. Med. Biol. Res. December 2015, 1(3): 457-462